2006
DOI: 10.1177/1073191105284279
|View full text |Cite
|
Sign up to set email alerts
|

Internal Consistency Reliability of the Self-Report Antisocial Process Screening Device

Abstract: The self-report version of the Antisocial Process Screening Device (APSD) has become a popular measure for assessing psychopathic features in justice-involved adolescents. However, the internal consistency reliability of its component scales (Narcissism, Callous-Unemotional, and Impulsivity) has been questioned in several studies. This study evaluates the internal consistency reliability of the self-report APSD by examining various indices (e.g., Cronbach's alpha, mean interitem correlation) across 11 studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
82
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 19 publications
13
82
2
Order By: Relevance
“…APSD total scores have demonstrated acceptable validity and reliability (α = .62 -81; Barry, Frick, & Killian, 2003); however, the internal consistency at the factor level has been less adequate: CU (α = .22 -.61); IMP (α = .44 -.68); NAR (α = .59 -.85) (Muñoz & Frick 2007;Poythress, Dembo, et al, 2006). Consistent with previous research (e.g., Lee et al, 2003;Poythress, Douglas, et al 2006, Poythress, Dembo, et al, 2006, the current study found that internal consistency was acceptable for the APSD total score (α = .73) and weaker for the factor scores (α = .51, .63, and .44 for IMP, NAR, and CU subscales, respectively).…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…APSD total scores have demonstrated acceptable validity and reliability (α = .62 -81; Barry, Frick, & Killian, 2003); however, the internal consistency at the factor level has been less adequate: CU (α = .22 -.61); IMP (α = .44 -.68); NAR (α = .59 -.85) (Muñoz & Frick 2007;Poythress, Dembo, et al, 2006). Consistent with previous research (e.g., Lee et al, 2003;Poythress, Douglas, et al 2006, Poythress, Dembo, et al, 2006, the current study found that internal consistency was acceptable for the APSD total score (α = .73) and weaker for the factor scores (α = .51, .63, and .44 for IMP, NAR, and CU subscales, respectively).…”
Section: Methodssupporting
confidence: 85%
“…However, these factor level differences were not present for the parent-rated APSD in a non-referred, community sample (Marsee, Silverthorn, & Frick, 2006). In offender samples, the CU subscale has demonstrated relatively poor internal consistency (α = .22 -.61) in comparison to the IMP (α = .44 -.68) and NAR (α = .59 -.85) subscales (Poythress, Dembo, et al, 2006;Poythress, Douglas, et al, 2006;Muñoz & Frick 2007), which may explain the weak association between APSD measured CU traits and antisocial behavior.…”
mentioning
confidence: 92%
“…However, youth tend to be the best reporters of many life events-and particularly those that are controllable (e.g., romantic and peer relationships)-that parents are less likely to have observed or which rely on individual interpretation of terms such as 'increased arguments between parents' (Allen et al, 2012). Second, like other studies using the self-report APSD (Poythress et al, 2006), internal consistencies for the CU scale were low in the present study (Cronbach's s = .50 -.60). It will be important for future studies to replicate these findings using newer and internally consistent measures of CU traits, such as the 24-item Inventory of Callous-Unemotional Traits (ICU; .…”
Section: Cu Traits and Negative Life Events 17mentioning
confidence: 97%
“…Although a number of measures for the assessment of psychopathy in children and adolescents are available (51,56,57), with respect to the assessment of CU traits, most of these measures include only a limited number of items, that specifically assess these traits, and have limited response options. Perhaps, this contributes to some of the psychometric shortcomings of some of these scales, such as relatively modest internal consistency (58) and restricted range of measurement (50). Furthermore, some of these measures are primarily suitable for use in offender samples; some are quite time-consuming and require specialist training to obtain reliable ratings (57).…”
Section: Assessment Of Callous-unemotional Traitsmentioning
confidence: 99%